2006
DOI: 10.1182/blood-2005-08-3289
|View full text |Cite
|
Sign up to set email alerts
|

Host factors that impact the biodistribution and persistence of multipotent adult progenitor cells

Abstract: Multipotent adult progenitor cells (MAPCs) are marrow-derived pluripotent stem cells with a broad differentiation potential. We sought to identify factors that affect adoptively transferred MAPCs. In vitro, MAPCs expressed low levels of major histocompatibility complex (MHC) antigens, failed to stimulate CD4 ؉ and CD8 ؉ T-cell alloresponses, and were targets of NK cytolysis. To study in vivo biodistribution, we labeled MAPCs with luciferase for sequential quantification of bioluminescence and DsRed2 for immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 29 publications
7
64
1
Order By: Relevance
“…29 An initial drawback of intravenous application is the large proportion of first-pass pulmonary sequestration. 30 Intra-arterial administration offers a method to further localize the placement of stem cells. However, recent investigation has shown that intracarotid infusion of MSCs induces ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…29 An initial drawback of intravenous application is the large proportion of first-pass pulmonary sequestration. 30 Intra-arterial administration offers a method to further localize the placement of stem cells. However, recent investigation has shown that intracarotid infusion of MSCs induces ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Animals treated intravenously were found to have reduced motor and neurological severity score deficits. 41 The administration of bone marrow-derived progenitor cells intraarterially, as opposed to intravenously, has been shown to lead to a significantly greater biodistribution in other laboratories, 72 but this could also lead to the development of cell emboli, decreasing blood flow. 16 After the success of the acute therapy, Chopp and coworkers subsequently reported that MSC therapy 1 week after TBI also led to long-term functional recovery (3 months after treatment) and that the cells remained in the brain at 3 months.…”
Section: Bone Marrow-derived Stem and Progenitor Cell Therapymentioning
confidence: 99%
“…These antibodies shut down T-lymphocyte responses, which are critical for long-term immunity and rejection of transplants. Since the ability of multipotent adult progenitor cells to survive after a transplant is diminished by the persistence and activity of T and B cells [6], Tilly's use of additional immunosuppressants may have favored survival and differentiation of bone marrow stem cells in the ovary. The bone marrow transplants themselves were not equivalent.…”
Section: Significance and Perspectivementioning
confidence: 99%
“…While Wagers' lab used whole bone marrow, Tilly's laboratory used a fraction of pluripotent bone marrow cells that was enriched for germline markers and lacked hematolymphoid commitment, which may have favored engraftment of transplanted cells in the ovary. Finally, the routes of bone marrow injection, which can affect engraftment of marrow cells [6], also differed in that Wagers used retro-orbital injection and Tilly used intravenous tail injection. This difference in injection sites could also explain why Wagers observed low-level hematolymphoid chimerism in the bone marrow recipients.…”
Section: Significance and Perspectivementioning
confidence: 99%